Practical methods in analyzing regional development indicators: Najaf province as a model - Al-Khazraji, Ammar Abdul Azim Shukr (Al-Adab Journal, 2020)
Regional development is the effective tool in reducing this disparity between the development indicators and achieving the level of prosperity of any region. It has been working on the regional redistribution of investments and spreading the fruits of development among different regions of the region in a fair manner. The study aims at measuring the degree of regional disparities in the areas of development in their economic and social sectors Najaf regions through the use of methods of descriptive and quantitative analysis, and the diagnosis of the degree of priority development between its regions, and the most important findings of the study is the lack of regional justice in the distribution of fits among individuals between the regions of the region, It was found that Najaf district is the best districts according to the developmental planning indicators adopted in the study, followed by the Kufa and Manathirah districts, and there was a strong positive relationship between population and the allocations at (0.98%). (-0.86%), and the main recommendations of the study is to be a priority in the development and development of the Kufa district with medium development indicators, And then comes Alnadhara in the category of low development indicators and then spend Najaf, which was within the category of indicators of development better through attention to the regional dimension in the distribution of government investments, giving the role of the private sector to establish various projects in disadvantaged and underdeveloped development and economic, and provide facilities to encourage them to investment in accordance with the potential and advantages available in them. And that investments should be directed towards basic services in all districts.